Evolutionary optical framework - NG-PON2: control and synchronization of ONUs via ICTP (Inter- Channel-Termination Protocol) - Vale, Patrícia Isabel Almeida Campino Martins do (2020)
The study of new technologies with the potential to support high transfer rates is important to respond to the constant evolution of Internet information consumption. The Next-Generation Passive Optical Networks (NG-PON) tries to overcome this obstacle. The most recent one, NG-PON2, uses several channels in the same fiber to transmit and receive data, considerably increasing the bandwidth of a single fiber. This new form of communication has introduced a new problem, the exchange of information between these channels with a minimum of disturbances on the network. The Inter-Channel-Termination Protocol (ICTP) was presented to certify that this communication is done correctly in a multi-operator environment. Based on a pre-built environment with the cooperative use of Gigabit PON (GPON) and NG-PON2 technologies, a system with similar characteristics to those of a real scenario was developed. In this system, two ICTP use cases were implemented and, for each one, two events were tested. The results obtained showed the possibility of being used in a real scenario, without failures and with small delays.